The Evaluation of Academic Writing Courses Using CIPP Model - Purnawati, Purnawati; Suseno, Muchas; Satiadi, Samsi (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
One of the most challenging disciplines for university students is academic writing. According to this assertion, a number of thesis advisors voiced their displeasure with the writing abilities of the students, pointing out numerous errors in syntax, vocabulary, main concept development, and other areas. Thus, evaluation on Academic Writing course in necessary. The purpose of this research is to apply the CIPP (Context, Input, Process, Product) assessment model to assess the learning process of Academic Writing courses in a state university in Tangerang. The Miles and Hubberman data analysis and descriptive evaluative data approach of the qualitative research method was used. strategies for gathering data that involve Questionnaire fulfilment, document analysis and interviews. Result showed that Context, Input, and Product of Academic writing courses gained Strongly agree to the indicators meaning very good implementation, while the aspect of process gained Agree that means Good implementation. However, students and lecturer are recommended to focus on only in the product of writing but also in the process as there was indication of students’ over-relying on AI writing generator such as ChatGPT dan Perplexity.